2020
DOI: 10.1017/s175173112000097x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of chemerin and its receptors (CMKLR1, GPR1, CCRL2) in the porcine uterus during the oestrous cycle and early pregnancy and in trophoblasts and conceptuses

Abstract: Recent research has demonstrated that chemerin may take part in the regulation of reproduction. The aim of this study was to determine the expression of chemerin system – chemerin and its receptors, chemokine-like receptor 1 (CMKLR1), G protein-coupled receptor 1 (GPR1) and C-C chemokine receptor-like 2 (CCRL2) – in the porcine uterus during the oestrous cycle and early pregnancy, and in trophoblasts and conceptuses by real-time PCR and western blotting. Chemerin concentrations in uterine luminal flushings (UL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…These genes are most related to cytokine-cytokine receptor interactions. Of those, CCRL2 has recently been implicated in the regulation of reproductive functions in pigs (Gudelska et al, 2020). The region on SSC 4 (63 Mb) has also previously been associated with number of piglets mummified in a large White population (Wu et al, 2019).…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%
“…These genes are most related to cytokine-cytokine receptor interactions. Of those, CCRL2 has recently been implicated in the regulation of reproductive functions in pigs (Gudelska et al, 2020). The region on SSC 4 (63 Mb) has also previously been associated with number of piglets mummified in a large White population (Wu et al, 2019).…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%
“…The expression of the chemerin system in the porcine reproductive tract during the estrous cycle and early gestation has been reported previously [ 23 ]. Chemerin, CMKLR1, GPR1, and CCRL2 have been detected in both the endometrium and the myometrium.…”
Section: Discussionmentioning
confidence: 98%
“…During this time, the direction of PGF 2α secretion is altered from endocrine to exocrine, and PGE 2 production is stimulated, which promotes the secretory functions of the corpus luteum and ensures the proper course of gestation [ 36 , 37 ]. During our previous study we indicated the changes of chemerin system protein expression across early gestation which may be caused by a number of factors present in the uterine microenvironment [ 23 ]. The analysis of the results presented herein indicates many similarities between the basal and PG-stimulated chemerin system expression patterns on the corresponding days of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations